Controlled attitude motion of the space tether system at the retraction tether stage. (10th November 2020) - Pikalov, Ruslan S.; Aslanov, Vladimir S.
This study focuses on the dynamics of a rendezvous of a tug and large space debris connected by a viscoelastic tether. It is assumed that control is realised by changing the length of the tether. The goal is to study the dynamic of the manoeuvre of the rendezvous and to find the ways, which allow to control the attitude motion of a space tether system. The results can be applied to the implementation of rendezvous of two bodies using the tether.